Kemenangan Partai Partai Aceh pada Pemilihan Legeslatif 2009 di Kabupaten Aceh Tamiang 2009 - P, Abdi Karya (Universitas Sumatera Utara, 2018)
This study is a study of the victory of local parties with a case study of Aceh Partys victory in legislative elections in Aceh Tamiang District 2009. The focus discusses why the Aceh Party (PA) can win the legislative elections in Aceh Tamiang District 2009. The method used is descriptive-qualitative method, The research are emphasized on giving an objective picture about the actual state of the object under study. However, in order to obtain broader benefits in this study, in addition to the fact also the provision of strong interpretations. With the technique of collecting interview data and documentation and data analysis techniques using descriptive analysis. The findings of this study include four things that are the factors winning the Aceh Party in the 2009 Election. First, the factors of political strategy; Secondly, there is a solid political machine; Third, the political culture of the people of Aceh Tamiang; Fourth, the political atmosphere. Furthermore, there were also four things to be the inhibiting factors experienced by the Aceh Party in the 2009 Election. Firstly, the funding factor; Secondly, the existence of intimidation; Third, party infrastructure; Fourth, 30% quota of female candidates.Â